Can nudge-interventions address health service overuse and underuse? Protocol for a systematic review. Issue 6 (24th June 2019) - O'Keeffe, Mary; Traeger, Adrian C; Hoffmann, Tammy; Ferreira, Giovanni Esteves; Soon, Jason; Maher, Christopher
Abstract : Introduction: Nudge-interventions aimed at health professionals are proposed to reduce the overuse and underuse of health services. However, little is known about their effectiveness at changing health professionals' behaviours in relation to overuse or underuse of tests or treatments. Objective: The aim of this study is to systematically identify and synthesise the studies that have assessed the effect of nudge-interventions aimed at health professionals on the overuse or underuse of health services. Methods and analysis: We will perform a systematic review. All study designs that include a control comparison will be included. Any qualified health professional, across any specialty or setting, will be included. Only nudge-interventions aimed at altering the behaviour of health professionals will be included. We will examine the effect of choice architecture nudges (default options, active choice, framing effects, order effects) and social nudges (accountable justification and pre-commitment or publicly declared pledge/contract). Studies with outcomes relevant to overuse or underuse of health services will be included. Relevant studies will be identified by a computer-aided search of the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library), MEDLINE, CINAHL, Embase and PsycINFO databases. Two independent reviewers will screen studies for eligibility, extract data and perform the risk of bias assessment using the criteria recommended by the Cochrane Effective Practice and Organisation of Care (EPOC) group. We will report our results in a structured synthesis format, as recommended by the Cochrane EPOC group. Ethics and dissemination: No ethical approval is required for this study. Results will be presented at relevant scientific conferences and in peer-reviewed literature.